The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jmoldx.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of the TheraTyper-GJB2 Assay for Detection of GJB2 Gene Mutations

Abstract: Mutations in the GJB2 gene are the most common cause of congenital hearing loss in many populations. This study describes the development of a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry-based minisequencing assay, TheraTyper-GJB2, for the detection of c.35delG, c.167delT, and c.235delC mutations in the GJB2 gene. This assay was evaluated for analytic performance, including detection limit, interference, cross-reactivity, and precision, using GJB2 reference standards prepared b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…The results revealed that 36 of the 117 patients (30.77%) carried two deafness-causing mutations, including the GJB2 gene mutations (16.24%), SLC26A4 gene mutations (10.26%) and mitochondrial DNA 12SrRNA 1555 locus mutation (4.27%). The 235delC mutation in the GJB2 gene mutation has been identified at the highest rate in patients in the present study and is also the most common in the Asian population ( 24 ). The present study identified the mitochondrial DNA 12S rRNA 1,555A>G locus mutation in ~4.27% of the patients, which follows the pattern of maternal inheritance ( 11 , 18 ).…”
Section: Discussionsupporting
confidence: 51%
“…The results revealed that 36 of the 117 patients (30.77%) carried two deafness-causing mutations, including the GJB2 gene mutations (16.24%), SLC26A4 gene mutations (10.26%) and mitochondrial DNA 12SrRNA 1555 locus mutation (4.27%). The 235delC mutation in the GJB2 gene mutation has been identified at the highest rate in patients in the present study and is also the most common in the Asian population ( 24 ). The present study identified the mitochondrial DNA 12S rRNA 1,555A>G locus mutation in ~4.27% of the patients, which follows the pattern of maternal inheritance ( 11 , 18 ).…”
Section: Discussionsupporting
confidence: 51%
“…The average of PPV and NPV were obtained from 12 reference articles where methods using matrix-assisted laser desorption ionization-time-of-flight mass spectrometry or real-time PCR were compared with Sanger sequencing in detecting mutations of GJB2 or other human genes. The average PPV and NPV were 96.7% and 92.5%, respectively, and the differences from the lower margin of the 95% CI (δ, the non-inferiority margin) were -4.7% and -6.5% respectively [2435]. Based on the reference articles, the sizes of positive and normal samples were calculated using the equation below, considering a 10% dropout rate.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned earlier, 50% of hearing impairment cases are caused by genetic factors and most of them are due to mutations in the GJB2 gene. Because GJB2 codes for the instructions of making the protein Cx26, any changes in its nucleotide sequence might either result in a change of amino acids or deleting some of them contributing to the translation of a connexin 26 with an abnormal structure [18]. This irregular structure of the protein, whether it is incomplete or lost an essential bond that connects it with other monomers, it will surely lead it to be a faulty protein as all of its structure components plays a key role in stabilizing it, and so making able to carry its normal function [18].…”
Section: Mutations In the Gjb2 Genementioning
confidence: 99%
“…According to recent research, the most common connexin 26 mutation is 35delG, and it is a frame shift mutation that involves the deletion of Guanine base at position 35, causing in a shifting of the sequence, and thus resulting in TGA, a premature stop codon. Consequently, the coding sequence is terminated resulting in a shortened Cx26 protein [18].…”
Section: Mutations In the Gjb2 Genementioning
confidence: 99%